Konsep Dasar Bagi Seorang Penari - Sutarno Haryono (Institut Seni Indonesia Surakarta, 2012)
There are two aspects which place emphasis on creativity as one of the main motivations of a dancer to increase his or her ability to project a creative interpretation, create empathy, and possess a social perspective. This emphasis includes the meaning of an idea which is reinforced through creative activity by looking at something with a broader perspective. The creative discovery of a dancer is essentially as important as developing ideas, and also the final result. As such, it is hoped that a dancer will determine and react to changes and developments in the art community by producing a personal interpretation in the form of a dance performance. Keywords : Basic concepts, Basic skills, and Dancer.